THE SIGNIFICANCE OF SOCIALLY ADEPT BEHAVIOR FOR ADVANCING CAREERS AND ENSURING LONG-TERM EMPLOYABILITY WITHIN ORGANIZATIONS (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2024)
Purpose: The aim of this paper is to highlight the increasing importance of social competencies in the business environment, with a particular focus on employee career advancement. The paper seeks to illustrate the significance of specific socially competent behaviors, evaluate their relevance across various industries, and assess how HR managers and top executives perceive these behaviors.Methodology: The study included a sample of 113 employers. Statistical analyses were conducted using t-tests for dependent and independent samples, ANOVA, and Cronbach’s alpha to ensure reliability.Results: No significant differences were observed between the tested socially competent behaviors in relation to career advancement. These behaviors are equally valued across industries and by both HR managers and top executives in the context of long-term employability.Conclusion: The findings underscore the importance of empathetic behavior as a key social competency for career progression and long-term employability, placing it on par with communication and conflict management skills. The study also indicates that empathy, communication, and conflict management are equally critical across all economic sectors, encouraging employers to invest in the development of these competencies regardless of their industry. Contrary to the assumption that HR managers prioritize empathy, communication, and conflict management more than top executives do, the research found no significant differences in their perspectives.